1988
DOI: 10.1177/154079698801300308
|View full text |Cite
|
Sign up to set email alerts
|

Generations of Hope: Parental Perspectives on the Transitions of Their Children with Severe Retardation from School to Adult Life

Abstract: Transitions within families are socially constructed processes that need to be understood in both their his torical and their cultural context. This study explored how parents interpret the events and relationships sur rounding the transition of their children with severe disabilities from school to adult life. The study used qualitative techniques to collect and analyze data from two sets of parents grouped according to their children's ages. Results indicated that the parents interviewed tended to perceive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 8 publications
1
44
0
Order By: Relevance
“…Parental involvement is fundamental during the transition decision-making process (Ferguson, Ferguson, & Jones, 1988). Parent participation throughout the IEP process has been linked to numerous beneficial outcomes, such as the development of positive parent and professional relationships, positive educational outcomes for students, and higher rates of employment after high school (Saliember & Furney, 1997;Test et al, 2009).…”
Section: Transition From Secondary Settingsmentioning
confidence: 99%
“…Parental involvement is fundamental during the transition decision-making process (Ferguson, Ferguson, & Jones, 1988). Parent participation throughout the IEP process has been linked to numerous beneficial outcomes, such as the development of positive parent and professional relationships, positive educational outcomes for students, and higher rates of employment after high school (Saliember & Furney, 1997;Test et al, 2009).…”
Section: Transition From Secondary Settingsmentioning
confidence: 99%
“…The transition to adulthood may imply changes in family relationships (Brotherston, Backus, Summers & Turnbull. 1986) and the renegotiation of service contacts, roles and responsibilities (Fergusson, Fergusson & Jones;. Wikler (1981Wikler ( , 1986 suggested that Downloaded by [Queensland University of Technology] at 10:53 14 October 2014 there are increased levels of parental stress associated with such social transitions, periodic reawakenings of the 'chronic sorrow' of having a child with a severe disability (Olshansky, 1962;Wikler, Wasow & Hatfield, 1981).…”
mentioning
confidence: 96%
“…Research suggests that parental stress heightens when they perceive themselves (or their child) to deviate from cultural norms -e.g. having more involvement in their child's adult life as opposed to the standard 'norm' of less involvement as their child transitions into adulthood (Ferguson, Ferguson and Jones, 1988). Additionally, the types of meaning that parents make when confronted by transitional stress (e.g., global versus situational) are suggested to have implications for parental adjustments, and for the wellbeing of their child and wider family system (Park, 2010).…”
Section: Introductionmentioning
confidence: 99%